Efek Moderasi Kapasistas SDM Hubungan Pemanfaatan TI terhadap Akuntabilitas Keuangan Pada OPD Kota Palu - Astrialestari Astrialestari; Rudy Usman; Masruddin Masruddin; Andi Mattulada Amir (Journal of Economics and Management Scienties, 2026)
This study aims to analyze the effect of information technology utilization on regional financial accountability and to examine the moderating effect of human resource capacity in this relationship. The study was conducted in 30 Regional Apparatus Organizations (OPD) in Palu City, involving 60 respondents consisting of regional financial management officials. A quantitative approach was used through a survey method with purposive sampling. Primary data were collected through questionnaires and analyzed using IBM SPSS Statistics version 25. The results showed that the use of information technology had a positive and significant effect on regional financial accountability, as did human resource capacity. However, the results of the moderation analysis showed that human resource capacity did not act as a moderating variable in the relationship between the use of information technology and regional financial accountability. These findings indicate that both variables function as independent factors that directly affect regional financial accountability. This study is expected to contribute theoretically to the development of public sector accounting studies and provide practical considerations for local governments in improving financial management accountability through the optimization of information technology and the enhancement of human resource capacity.